A castable phosphate gradient composite and a method of making the same

CN122958192APending Publication Date: 2026-10-23CENT SOUTH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611459848.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-20
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]针对现有的多层结构磷酸盐防隔热材料存在的界面易分层、组装复杂和热稳定差等问题,本发明的第一个目的是在于提供一种浇筑式磷酸盐梯度复合材料,通过向层状结构的磷酸盐材料中引入纤维管协同不同磷酸盐层之间成分的改进,使得材料兼具优异耐烧蚀和隔热性能的同时,还解决了传统堆叠材料层间易剥离的难题

Benefits of technology

[0032](1)本发明利用磷酸盐的常温固化性和流动性实现多功能一体化,各分区功能由浇筑浆料决定。防热层利用硼改锆基磷酸盐浆料优异的高温抗烧蚀性能,协同抵抗烧蚀火焰的侵蚀;过渡层利用混杂短切纤维提高材料整体承载性能,并起到连接和固定防热层的隔热层,另外利用有机物的高温分解特性,提高内部压力阻挡烧蚀热量的内渗传导;隔热层利用空心微珠的低热导率,将大部分热量隔绝在过渡层,从而起到保护作用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958192A_ABST
    Figure CN122958192A_ABST
Patent Text Reader

Abstract

The application discloses a kind of casted phosphate gradient composite material and preparation method thereof, belong to the field of ablation-resistant material.The material includes quartz fiber tube and phosphate material;The quartz fiber tube is woven from quartz fiber bundle, with hollow tubular structure;The phosphate material is fixed on the outer surface of quartz fiber tube and hollow tubular structure by pouring;The phosphate material has three-layer structure, the middle layer is transition layer, and the two sides are heatproof layer and heat insulation layer respectively.The application introduces fiber tube into layered structure phosphate material, improves the composition between different phosphate layers, and pours in the mode, so that the material has excellent ablation resistance and heat insulation performance, and also solves the problem of easy peeling between traditional stacked material layers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ablation-resistant materials and relates to a cast-type phosphate gradient composite material and its preparation method. Background Technology

[0002] With the rapid development of aerospace, high-speed aircraft, and nuclear energy industries, the demand for high-performance thermal insulation materials is becoming increasingly urgent. Currently, commonly used thermal insulation materials mainly include ceramic matrix composites such as silicon carbide matrix composites, carbon / carbon composites, and various ablation materials. These materials typically possess excellent high-temperature resistance; for example, carbon / carbon composites can withstand temperatures above 3000℃ in an inert atmosphere, and ceramic matrix composites also exhibit good oxidation resistance and high-temperature strength. However, in extreme thermo-mechanical coupling environments, traditional materials often reveal significant shortcomings. For instance, due to limited thermal insulation performance, high thermal conductivity leads to rapid heat transfer, making it difficult to meet the requirements for long-term, high-efficiency thermal protection. Furthermore, their mechanical load-bearing capacity decreases sharply under high-temperature gradients, making them prone to thermal stress damage. They also suffer from poor thermal shock stability, easily developing cracks or even spalling during rapid temperature rises and falls. In addition, the preparation processes of existing materials are generally complex; processes such as chemical vapor infiltration and precursor impregnation pyrolysis are time-consuming, energy-intensive, and expensive, severely restricting their large-scale engineering application.

[0003] To overcome the aforementioned shortcomings, researchers have attempted to develop phosphate-based thermal insulation materials. Phosphates possess high thermal stability and bonding properties, and their preparation process is relatively simple, making them a research hotspot in recent years. Currently, multi-layered phosphate thermal insulation materials have been reported, combining different functional layers to balance thermal insulation and load-bearing requirements. For example, Chinese patent application CN117024163A discloses a variable-gradient ablation-resistant integrated phosphate composite material, which combines high-temperature resistance, low thermal conductivity, and high stability by stacking three layers of phosphate materials with different densities and thermal resistance properties. However, this method results in insufficient interlayer bonding strength in the multi-layered structure, making it prone to delamination failure under thermal cycling or mechanical vibration conditions. Furthermore, the multi-layer assembly process is complex, requiring stringent interface control, making efficient and reliable integrated molding difficult. Additionally, the interfacial thermal mismatch caused by differences in the thermophysical properties of each layer further reduces the overall thermal stability of the structure, limiting its long-term service life under harsh environments. Summary of the Invention

[0004] To address the problems of easy delamination at the interface, complex assembly, and poor thermal stability in existing multilayer phosphate thermal insulation materials, the first objective of this invention is to provide a castable phosphate gradient composite material. By introducing fiber tubes into the layered phosphate material to improve the composition between different phosphate layers, the material not only has excellent ablation resistance and thermal insulation performance, but also solves the problem of easy delamination between layers in traditional stacked materials.

[0005] The second objective of this invention is to provide a method for preparing cast-type phosphate gradient composite materials, which is simple in process, requires low equipment, and uses readily available raw materials.

[0006] To achieve the above-mentioned technical objectives, the present invention provides a castable phosphate gradient composite material, which includes a quartz fiber tube and a phosphate material; the quartz fiber tube is woven from quartz fiber bundles and has a hollow tubular structure; the phosphate material is cast and fixed to the outer surface of the quartz fiber tube and the hollow tubular structure; the phosphate material has a three-layer structure, with a middle transition layer, and two outer heat-resistant and heat-insulating layers respectively; the heat-resistant layer is obtained by mixing and curing boron-modified zirconium-based phosphate slurry, chopped fibers, and hollow microspheres; the transition layer and the heat-insulating layer are both obtained by mixing and curing boron-modified zirconium-based phosphate slurry, resin-based organic matter, chopped fibers, and hollow microspheres; and the amount of chopped fibers and hollow microspheres increases from the heat-resistant layer to the heat-insulating layer; the boron-modified zirconium-based phosphate slurry is obtained by mixing raw materials including aluminum phosphate, zirconium oxide, boric acid, and urea.

[0007] This invention relates to a castable phosphate gradient composite material with a quartz fiber tube as the matrix and a frame structure. Different components of phosphate slurry are cast in sections from bottom to top, forming a heat-resistant layer, a transition layer, and a heat-insulating layer in sequence. These layers are tightly bonded, giving the material excellent load-bearing capacity, ablation resistance, and heat insulation properties. Specifically, this invention uses quartz fiber tubes as the skeleton, primarily utilizing their advantages of being lightweight, high-temperature resistant, low thermal conductivity, and acid and alkali resistant. Furthermore, quartz fibers can form a good interfacial bond with phosphate, which is beneficial for improving the overall integrity of the material and the interlayer bonding strength. During the high-temperature ablation process, the boron-modified zirconium-based phosphate slurry in the heat-resistant layer decomposes and melts, generating ZrO2 and molten aluminum phosphate. Simultaneously, the chopped fibers in the heat-resistant layer melt into a viscous silica liquid, which can effectively adhere to zirconium oxide particles. In addition, the presence of the quartz fiber tubes can fix the molten and particulate matter, preventing its excessive dissipation. The generated ZrO2 layer can resist the erosion of the material's interior by the ablation flame, and the aforementioned decomposition and melting processes consume heat, thereby reducing heat penetration inwards. The transition layer incorporates chopped fibers, which enhance the material's mechanical load-bearing capacity through a hybrid effect and strengthen the connection between the heat-insulating and heat-resistant layers—the chopped fibers are mixed and distributed between the two layers, providing a good bridging effect. Furthermore, the transition layer slurry contains additional organic matter compared to the heat-insulating layer slurry. This is because the decomposition of resin-based organic matter during ablation generates pyrolysis gases, creating pressure within the transition layer and preventing the inward conduction of surface ablation heat, further improving heat insulation performance. The heat insulation layer further increases the amount of fibers and hollow microspheres in the transition layer slurry. The excellent heat insulation properties of the hollow microspheres effectively prevent the continued infiltration of residual heat from the transition layer.

[0008] Traditional stacked structures typically rely on interfacial bonding forces between layers to maintain integrity. However, these interfaces are often planar, making them prone to crack formation and propagation under thermal stress, mechanical impact, or prolonged use, ultimately leading to interlayer delamination. This invention, by introducing quartz fiber tubes, effectively forms a through- or semi-through three-dimensional reinforcing skeleton within the material. Instead of relying solely on interfacial planar bonding, the fiber tubes connect the material layers along their thickness through encapsulation, interlocking, and mechanical bonding with the matrix material. When the material is subjected to external forces or thermal stress, the stress originally concentrated at the interfacial interface can be dispersed and transferred along the quartz fiber tubes, thereby reducing stress concentration at the interface. Even if microcracks develop locally, the quartz fiber tubes can act as a barrier and bridge to prevent crack propagation, delaying further crack propagation along the interfacial direction. Therefore, this significantly improves the interfacial bonding strength and overall structural stability of the composite material. Furthermore, quartz fibers themselves possess characteristics such as high temperature resistance, low thermal expansion, and good chemical stability. When materials are used in environments with varying temperatures, quartz fiber tubes can reduce interfacial shear stress caused by differences in the coefficients of thermal expansion between different material layers, further reducing cracking, warping, and delamination problems caused by thermal cycling. Therefore, this invention, through the structural connection effect of quartz fiber tubes in the thickness direction, transforms the traditional two-dimensional layered bonding into a more stable three-dimensional integral reinforced structure, thereby effectively avoiding the interlayer delamination problem of traditional stacked structures.

[0009] In this invention, the quartz fiber tube is woven from quartz fiber bundles. Specifically, a portion of the quartz fiber bundles are laid flat and bound together to form a tube, while the remaining portion of the quartz fiber bundles are tightly wound around the outer surface of the cylindrical tube to form a hollow tubular structure.

[0010] As a preferred embodiment, the inner diameter of the quartz fiber tube is 10-20 mm. The inner diameter of the quartz fiber tube has a certain influence on the filling and coating effect of the matrix material on the quartz fiber tube, and further affects the interlayer bonding performance of the material. When the inner diameter of the quartz fiber tube is too small, the matrix material is difficult to fully enter the interior of the quartz fiber tube during the casting process, resulting in insufficient filling, residual air bubbles, or local voids, which weakens the mechanical interlocking and anchoring effect between the quartz fiber tube and the matrix material. Conversely, when the inner diameter of the quartz fiber tube is too large, the space occupied by the quartz fiber tube per unit volume of material is too large, and the thickness of the matrix material between tubes or between the tube and the material boundary is correspondingly reduced, making it difficult for the matrix material to form a uniform and continuous load-bearing structure, and easily causing stress concentration around the tube, which is detrimental to improving the interlayer bonding strength. A further preferred inner diameter is 10-16 mm.

[0011] As a preferred embodiment, the thickness ratio of the heat-insulating layer, transition layer, and insulation layer is (3~6):(1~4):(3~9). Within the above thickness ratio range, the material exhibits excellent load-bearing, ablation resistance, and thermal insulation performance. When the thickness of the heat-insulating layer is too low, the ablation resistance and erosion resistance of the outer surface of the material are insufficient, and surface ablation is easily aggravated under high-temperature high-speed airflow or thermal shock. When the thickness of the transition layer is too low, there is a lack of sufficient connection and buffer area between the heat-insulating layer and the insulation layer, resulting in abrupt changes in interlayer performance. This easily leads to interfacial stress concentration during heating or stress, causing interlayer cracking, debonding, or peeling. When the thickness of the insulation layer is too low, the thermal barrier capacity of the material is insufficient, and heat is easily transferred to the back of the material, causing the back temperature to rise, making it difficult to meet the thermal insulation protection requirements. A further preferred thickness ratio is (3~5):(3~4):(8~9).

[0012] As a preferred embodiment, the chopped fibers include at least one of alumina, quartz fiber, and carbon fiber; the hollow microspheres include at least one of ceramic hollow microspheres and glass hollow microspheres; and the resinous organic material includes at least one of phenolic resin, epoxy resin, and furan resin.

[0013] As a preferred embodiment, the aluminum-containing phosphate includes at least one of aluminum dihydrogen phosphate and aluminum chromium phosphate.

[0014] Further optimization of the chopped fibers into quartz fibers allows for the utilization of their material consistency with quartz fiber tubes, significantly enhancing the melting of the material during the ablation process and thus strengthening the overall integrity of the material.

[0015] As a preferred embodiment, the heat-resistant layer is obtained by mixing and curing boron-modified zirconium-based phosphate slurry, chopped fibers, and hollow microspheres in a mass ratio of (50~80):(0.5~4):(0.5~4). The high proportion of boron-modified zirconium-based phosphate slurry in the heat-resistant layer of this invention gives the material excellent high-temperature ablation resistance. Adding a small amount of chopped fibers increases the fluidity of the slurry, making it more suitable for casting. If too much chopped fiber is used in the heat-resistant layer, entanglement and agglomeration can easily occur between the fibers, reducing the uniformity of the slurry system, causing localized fiber enrichment, increased porosity, or molding defects, and hindering the formation of a continuous, dense, ablation-resistant structure. Conversely, excessive use of hollow microspheres, due to their hollow structure, reduces the overall density and load-bearing capacity of the material, leading to problems such as microsphere breakage and accelerated ablation. A further preferred mass ratio is (50~60):(0.5~1):(0.5~1).

[0016] As a preferred embodiment, the transition layer is formed by mixing and curing boron-modified zirconium-based phosphate slurry, resin-based organic materials, chopped fibers, and hollow microspheres in a mass ratio of (50~80):(2~10):(1~5):(1~5). The addition of resin-based organic materials to the transition layer utilizes their high-temperature decomposition characteristics to increase internal pressure and prevent the infiltration and conduction of ablation heat. The addition of a moderate amount of chopped fibers enhances the overall load-bearing capacity of the material and also serves as a heat insulation layer connecting and fixing the heat-resistant layer. A further preferred mass ratio is (50~60):(3~5):(1~2):(1~2).

[0017] As a preferred embodiment, the heat insulation layer is formed by mixing and curing boron-modified zirconium-based phosphate slurry, resin-based organic materials, chopped fibers, and hollow microspheres in a mass ratio of (50~80):(2~10):(1~6):(1~6). Adding a higher amount of hollow microspheres and chopped fibers to the heat insulation layer can significantly reduce thermal conductivity, thereby further isolating heat transfer. A further preferred ratio is (50~60):(3~5):(1.5~3):(1.5~3).

[0018] As a preferred embodiment, the boron-modified zirconium-based phosphate slurry contains aluminum phosphate, zirconium oxide, boric acid, and urea in a mass ratio of (20~30):(40~60):(1~5):(1~3), and the mixing time is 20~30 min to obtain a uniformly dispersed sol solution. The boron-modified zirconium-based phosphate slurry of this invention utilizes aluminum phosphate as a binder component to coat zirconium oxide, fibers, and hollow microspheres, enhancing the integrity of each layer and interlayer bonding. Simultaneously, zirconium oxide can form a high-temperature resistant skeleton within the layers, improving erosion and ablation resistance. Boric acid, as a boron-modified component, can generate a boron-containing glassy phase or composite oxide at high temperatures, filling and repairing microcracks and inhibiting oxidation and thermal intrusion. The introduced urea improves slurry dispersibility, reduces powder agglomeration, promotes uniform reaction, and alleviates shrinkage stress during curing, reducing the risk of cracking. The synergistic effect of these components results in superior overall material performance. The optimal mass ratio is (22~28):(48~55):(1~3):(1~2).

[0019] This invention also provides a method for preparing a cast-type phosphate gradient composite material, comprising the following steps:

[0020] S1 mixes boron-modified zirconium-based phosphate slurry with chopped fibers and hollow microspheres to obtain a heat-resistant layer casting slurry; the heat-resistant layer slurry is cast into the hollow tubular structure and outer surface of a quartz fiber tube, and after vibration and curing, a block sample 1 is obtained;

[0021] S2 mixes boron-modified zirconium-based phosphate slurry, resin-based organic matter, chopped fibers and hollow microspheres to obtain a transition layer casting slurry; the transition layer slurry is then cast onto block sample 1, and after vibration and curing, block sample 2 is obtained;

[0022] S3 mixes boron-modified zirconium-based phosphate slurry, resin-based organic matter, chopped fibers and hollow microspheres to obtain a heat insulation layer casting slurry; the heat insulation layer slurry is then cast onto block sample 2, and after vibration and curing, the desired result is obtained.

[0023] In S1, S2 and S3, the amounts of the chopped fibers and hollow microspheres increase sequentially.

[0024] The preparation method of this invention is simple, requires low-level equipment, and has simple preparation conditions, with a low overall processing temperature. Furthermore, it utilizes the room-temperature curing and flowability of phosphates to achieve multifunctional integration, with the function of each zone determined by the impregnation slurry.

[0025] In actual operation, a mold can be fitted onto the outer surface of the quartz fiber tube to fix and shape the phosphate slurry poured on the outer surface.

[0026] As a preferred embodiment, the quartz fiber tube undergoes ultrasonic cleaning pretreatment for 5-8 minutes before use. Appropriate ultrasonic cleaning pretreatment can remove impurities from the quartz fiber tube, ensuring the purity of the obtained material.

[0027] As a preferred embodiment, in S1, the mixing time is 5-10 minutes, the curing temperature is 60-90°C, and the curing time is 1-2 hours. A further preferred mixing method is stirring. Within the mixing time range of this invention, short fibers, hollow microspheres, and boron-modified zirconium-based phosphate slurry can be mixed uniformly, avoiding fiber agglomeration that could affect the casting effect. Furthermore, by controlling the curing temperature and time, a block without cracks or porous structures can be obtained.

[0028] As a preferred embodiment, in S2 and S3, the mixing time is 8-15 minutes, the curing temperature is 60-90°C, and the curing time is 1-2 hours. A further preferred mixing method is stirring.

[0029] As a preferred embodiment, the viscosity of the heat-insulating layer casting grout, the transition layer casting grout, and the heat-insulating layer casting grout are all controlled within 100~300 mp·s. This invention, by controlling the viscosity of the grout in each layer, helps to ensure the flowability, component dispersion stability, and interlayer bonding effect during the casting process.

[0030] Further preferably, the viscosity difference between two adjacent layers of grout does not exceed 100 mPa·s, more preferably not exceeding 50 mPa·s. By controlling the viscosity difference between the three grouts, each layer can maintain similar flow behavior during continuous or step-by-step casting, avoiding interface defects caused by excessive differences in flowability, and forming a stable and continuous bonding interface between the heat-insulating layer, transition layer, and heat-resistant layer.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) This invention utilizes the room temperature curing and fluidity of phosphates to achieve multifunctional integration, with the function of each zone determined by the casting slurry. The heat-insulating layer utilizes the excellent high-temperature ablation resistance of boron-modified zirconium-based phosphate slurry to synergistically resist the erosion of ablation flames; the transition layer utilizes mixed short-cut fibers to improve the overall load-bearing capacity of the material and serves as a heat insulation layer to connect and fix the heat-insulating layer. In addition, it utilizes the high-temperature decomposition characteristics of organic matter to increase internal pressure and block the infiltration and conduction of ablation heat; the heat insulation layer utilizes the low thermal conductivity of hollow microspheres to isolate most of the heat in the transition layer, thereby playing a protective role.

[0033] (2) By introducing fiber tubes into the layered phosphate material to improve the composition between different phosphate layers, the present invention enables the material to have both excellent ablation resistance and heat insulation properties, while solving the problem of easy peeling between layers of traditional stacked materials.

[0034] (3) The phosphate material of the present invention showed no damage after being subjected to oxyacetylene ablation at 2500℃ for 120s, and is particularly suitable for use in extreme thermo-mechanical coupling environments.

[0035] (4) The preparation method of the present invention employs a casting method, which allows the matrix material to fully cover the quartz fiber tube and fill the spaces between material layers during the molding process, thereby forming a continuous and dense integral structure. Compared with the traditional impregnation method, the casting method does not rely solely on capillary penetration, and can significantly reduce porosity, dry spots, and interface defects caused by insufficient wetting, thereby improving the bonding strength between the quartz fiber tube and the matrix, and enabling the reinforcing structure and the matrix material to form a more reliable mechanical interlocking and interfacial bond. This results in the material obtained by the present invention having higher interlayer peel resistance, mechanical stability, and thermal shock resistance. Attached Figure Description

[0036] Figure 1 This is a schematic diagram illustrating the preparation of a cast-type phosphate gradient composite material according to the present invention.

[0037] Figure 2 This is a cross-sectional view of the FCZ prepared in Example 1.

[0038] Figure 3The images show the cross-sectional microstructure of the FCZ prepared in Example 1, where (a) is a low-magnification SEM image of the heat-insulating layer, (b) is a high-magnification SEM image of the heat-insulating layer, (c) is a low-magnification SEM image of the transition layer, (d) is a high-magnification SEM image of the transition layer, (e) is a low-magnification SEM image of the heat-insulating layer, and (f) is a high-magnification SEM image of the heat-insulating layer.

[0039] Figure 4 The shear strength properties of FCZ-1 prepared in Example 2 and CZ prepared in Comparative Example 1 are shown in the figure.

[0040] Figure 5 The ablation surface temperature and back surface temperature of the samples during the ablation process of FCZ prepared in Example 1 at 2500℃ for 60s, FCZ-1 prepared in Example 2 at 2500℃ for 120s, and CZ prepared in Comparative Example 1 at 2500℃ for 60s are shown. (a) is the ablation surface temperature, (b) is the ablation back surface temperature, and the dashed line represents the horizontal line of the highest point.

[0041] Figure 6 The images show the surface microstructure of FCZ-1 prepared in Example 2 after ablation at 2500℃ for 120s. (a) is a low-magnification SEM image of the ablation center region, (b) is a high-magnification SEM image of the ablation center region, (c) is a low-magnification SEM image of the ablation transition region, (d) is a high-magnification SEM image of the ablation transition region, (e) is a low-magnification SEM image of the ablation edge region, and (f) is a high-magnification SEM image of the ablation edge region.

[0042] Figure 7 Macroscopic morphology of the cross section of FCZ-1 prepared in Example 2 after ablation at 2500℃ for 120s.

[0043] Figure 8 The images show the cross-sectional microstructure of FCZ-1 prepared in Example 2 after ablation at 2500℃ for 120s. Among them, (a) is a low-magnification SEM image of the cross-section of the heat-insulating layer after ablation, (b) is a high-magnification SEM image of the cross-section of the heat-insulating layer after ablation, (c) is a low-magnification SEM image of the cross-section of the transition layer after ablation, (d) is a high-magnification SEM image of the cross-section of the transition layer after ablation, (e) is a low-magnification SEM image of the cross-section of the heat-insulating layer after ablation, and (f) is a high-magnification SEM image of the cross-section of the heat-insulating layer after ablation.

[0044] Figure 9 The macroscopic morphology of the cross section of CZ prepared for Comparative Example 1 after ablation at 2500℃ for 60s. Detailed Implementation

[0045] To further illustrate the present invention, the following detailed description of the integrated heat-insulating and load-bearing cast-in-place fiber composite phosphate material, its preparation method, and its application are provided in conjunction with embodiments. However, it should be understood that these embodiments are implemented under the premise of the technical solution of the present invention, and provide detailed implementation methods and specific operating procedures. They are only for further illustrating the features and advantages of the present invention, and are not intended to limit the patent of the present invention. The scope of protection of the present invention is not limited to the following embodiments.

[0046] The room temperature referred to in the embodiments and comparative examples of this invention is 25°C.

[0047] The quartz fiber tubes used in the embodiments and comparative examples of this invention were all purchased from Hubei Feilihua Quartz Glass Co., Ltd., with the trade name FQSL. They are woven from quartz fiber bundles and have a hollow tubular structure. The phenolic resin was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0048] Example 1

[0049] A method for preparing a cast-type phosphate gradient composite material comprises the following steps:

[0050] S1 ultrasonic cleaning of quartz fiber tube (inner diameter 16mm) for 8 minutes, oven drying, ready for use.

[0051] S2 weighs 27g aluminum dihydrogen phosphate, 55g nano ZrO2, 3g boric acid, 1g urea and 60ml distilled water, and ultrasonically disperses them for 25min to obtain boron-modified zirconium-based phosphate slurry.

[0052] S3 weighed 50g of boron-modified zirconium-based phosphate slurry, 0.5g of chopped quartz fiber and 0.5g of glass hollow microspheres, mixed and stirred for 8min to obtain a heat-insulating layer casting slurry with a viscosity of 100-180mp·s; the heat-insulating layer casting slurry was poured into the hollow tubular structure and outer surface of a quartz fiber tube with a mold (the inner diameter of the mold is 30mm) on the outer surface at room temperature, and the thickness was controlled to be 6mm. After casting, the tube was vibrated on a vibration table for 30min, and finally placed in a 70℃ oven for curing for 2h to obtain block sample I.

[0053] S4 weighs 50g of boron-modified zirconium-based phosphate slurry, 3g of phenolic resin, 1g of chopped quartz fiber, and 1g of glass hollow microspheres, mixes and stirs for 10 minutes to obtain a transition layer casting slurry with a viscosity of 130–200 mp·s. The transition layer casting slurry is then poured onto block sample I at room temperature, controlling the thickness to 4mm. After pouring, the sample is placed on a vibration table and vibrated for 30 minutes, then cured at 70℃ for 2 hours to obtain block sample II.

[0054] S5 weighs 50g of boron-modified zirconium-based phosphate slurry, 3g of phenolic resin, 2g of chopped quartz fiber, and 2g of glass hollow microspheres, mixes and stirs for 10 minutes to obtain a heat insulation layer casting slurry with a viscosity of 150–220 mp·s. The heat insulation layer casting slurry is directly cast onto block sample II at room temperature, controlling the thickness to 8mm. After casting, it is placed on a vibration table and vibrated for 30 minutes, then placed in an oven at 80℃ for 2 hours to cure, obtaining a cast-type phosphate gradient composite material, named FCZ.

[0055] The cast-type phosphate gradient composite material obtained in this embodiment showed no damage after being subjected to oxyacetylene ablation at 2500℃ for 60 seconds. The highest back temperature was 67.7℃, the shear strength was 11.3 MPa, and the thermal conductivity was 0.17 W / (m•K).

[0056] Example 2

[0057] A method for preparing a cast-type phosphate gradient composite material comprises the following steps:

[0058] S1 ultrasonic cleaning of quartz fiber sleeve (inner diameter 16mm) for 8 minutes, then oven drying for later use.

[0059] S2 weighs 30g aluminum dihydrogen phosphate, 60g nano ZrO2, 3g boric acid, 1g urea and 60ml distilled water, and ultrasonically disperses them for 25min to obtain boron-modified zirconium-based phosphate slurry.

[0060] S3 weighed 60g of boron-modified zirconium-based phosphate slurry, 1g of chopped quartz fiber and 1g of glass hollow microspheres, mixed and stirred for 8min to obtain heat-insulating layer casting slurry with a viscosity of 100-180mp·s; the heat-insulating layer casting slurry was cast into the hollow tubular structure and outer surface of a quartz fiber tube with a mold (the inner diameter of the mold is 30mm) on the outer surface at room temperature, and the thickness was controlled to be 5mm. After casting, the tube was vibrated on a vibrating table for 30min, and finally placed in a 70℃ oven for curing for 2h to obtain block sample I.

[0061] S4 weighs 60g of boron-modified zirconium-based phosphate slurry, 3g of phenolic resin, 1.5g of chopped quartz fiber, and 1.5g of glass hollow microspheres, mixes and stirs for 10 minutes to obtain a transition layer casting slurry with a viscosity of 130–200 mp·s. The transition layer casting slurry is then poured onto block sample I at room temperature, controlling the thickness to 4mm. After pouring, the sample is placed on a vibration table and vibrated for 30 minutes, then cured at 70℃ for 2 hours to obtain block sample II.

[0062] S5 weighs 50g of boron-modified zirconium-based phosphate slurry, 3g of phenolic resin, 2.5g of chopped quartz fiber, and 2.5g of glass hollow microspheres, mixes and stirs for 10 minutes to obtain a heat insulation layer casting slurry with a viscosity of 150–220 mp·s. The heat insulation layer casting slurry is directly cast onto block sample II at room temperature, controlling the thickness to 9mm. After casting, it is placed on a vibration table and vibrated for 30 minutes, then placed in an oven at 80℃ for 2 hours to cure, obtaining a castable phosphate gradient composite material, named FCZ-1.

[0063] The cast-type phosphate gradient composite material obtained in this embodiment showed no damage after 120s of oxyacetylene ablation at 2500℃. The highest back temperature was 74.9℃, the shear strength was 12.1 MPa, and the thermal conductivity was 0.21 W / (m•K).

[0064] Example 3

[0065] The only difference between this embodiment and Embodiment 2 is that the inner diameter of the quartz fiber tube is replaced with 20 mm. All other steps and conditions are the same, resulting in a cast-type phosphate gradient composite material.

[0066] The cast-type phosphate gradient composite material obtained in this embodiment showed no damage after 120 seconds of oxyacetylene ablation at 2500℃. The highest back temperature was 106.8℃, the shear strength was 10.9 MPa, and the thermal conductivity was 0.19 W / (m•K). An excessively large inner diameter caused detachment during the ablation process, leading to an increase in back temperature.

[0067] Example 4

[0068] The only difference between this embodiment and Embodiment 2 is that the inner diameter of the quartz fiber tube is replaced with 10 mm. All other steps and conditions are the same, resulting in a cast-type phosphate gradient composite material.

[0069] The cast-type phosphate gradient composite material obtained in this embodiment showed no damage after 120s of oxyacetylene ablation at 2500℃. The highest back temperature was 68.9℃, the shear strength was 8.8 MPa, and the thermal conductivity was 0.12 W / (m•K).

[0070] Example 5

[0071] The only difference between this embodiment and Embodiment 2 is that the short-cut quartz fibers are replaced with short-cut carbon fibers of equal mass, and the glass hollow microspheres are replaced with ceramic hollow microspheres of equal mass. All other steps and conditions are the same, resulting in a cast-type phosphate gradient composite material.

[0072] The cast-type phosphate gradient composite material obtained in this embodiment showed no damage after being subjected to oxyacetylene ablation at 2500℃ for 120s. The highest back temperature was 88.6℃, the shear strength was 10.5 MPa, and the thermal conductivity was 0.26 W / (m•K).

[0073] Example 6

[0074] This embodiment provides a method for preparing a castable phosphate gradient composite material. The raw material composition, thickness of each functional layer, and overall preparation steps are basically the same as in Example 2. The difference lies in adjusting the viscosity of each layer's casting slurry by adding a portion of distilled water, resulting in a larger viscosity difference between the casting slurries of adjacent functional layers. Specifically, the viscosity of the heat-insulating layer casting slurry is 100–120 mPa·s, the viscosity of the transition layer casting slurry is 250–270 mPa·s, and the viscosity of the heat-insulating layer casting slurry is 120–140 mPa·s.

[0075] The cast-type phosphate gradient composite material obtained in this embodiment showed no damage after being subjected to oxyacetylene ablation at 2500℃ for 120s. The highest back temperature was 86.2℃, the shear strength was 10.2 MPa, and the thermal conductivity was 0.24 W / (m•K).

[0076] Comparative Example 1

[0077] The only difference between this comparative example and Example 2 is that no quartz fiber tube was added. All other steps and conditions were the same as in Example 2, resulting in a cast-type phosphate gradient composite material, named CZ.

[0078] Comparative Example 2

[0079] The only difference between this comparative example and Example 2 is that boric acid is not added in S2. All other steps and conditions are the same as in Example 2, resulting in a cast-type phosphate gradient composite material.

[0080] The results show that the ablation layer without boric acid is prone to edge spalling under oxyacetylene flame. This is mainly due to the high temperature, high heat flux density, and rapid heating rate of the oxyacetylene flame, which quickly creates a large temperature gradient between the heated surface and the interior of the material, resulting in significant thermal stress. Simultaneously, at high temperatures, the phosphate-bound phase undergoes dehydration, condensation, and structural rearrangement, accompanied by a certain volume shrinkage; the thermal expansion mismatch between different components further exacerbates local stress concentration. Because the edge region of the sample is less constrained, cracks are more likely to initiate here and propagate along the weak particle / bound phase interface. Under the continuous scouring action of the high-speed oxyacetylene flame, cracked or weakly bonded areas are more prone to local peeling and blocky detachment.

[0081] Comparative Example 3

[0082] The only difference between this comparative example and Example 2 is that S4 is not performed. All other steps and conditions are the same as in Example 2, resulting in a cast-type phosphate gradient composite material.

[0083] The cast-type phosphate gradient composite material obtained in this comparative example, after oxyacetylene ablation at 2500℃ for 120 s, exhibited a maximum back temperature of 95.6℃ and a shear strength of 8.9 MPa. The results indicate that removing the S4 transition layer results in a direct bond between the heat-insulating and heat-resistant layers. This not only lacks the thermal resistance provided by the transition layer itself, but also leads to more pronounced abrupt changes in composition, fiber / microsphere content, and resin content between adjacent layers. Consequently, both interface matching and overall thermal insulation performance decrease.

[0084] Comparative Example 4

[0085] The only difference between this comparative example and Example 2 is that the order of S4 and S5 is reversed (that is, the positions of the transition layer and the insulation layer are reversed). All other steps and conditions are the same as in Example 2, resulting in a cast-in-place phosphate gradient composite material.

[0086] The cast-type phosphate gradient composite material obtained in this comparative example, after 120 s of oxyacetylene ablation at 2500℃, had a maximum back temperature of 85.3℃ and a shear strength of 10.3 MPa. The results indicate that although the composition and total thickness of the three layers remained unchanged, altering only the order of the transition layer and the insulation layer led to direct contact between the insulation and the heat-insulating layer. This increased the differences in composition, thermophysical properties, and mechanical properties between adjacent layers, making them more prone to interfacial stress concentration during curing and high-temperature ablation. This is detrimental to stable interlayer bonding and also results in an increase in back temperature.

[0087] Comparative Example 5

[0088] The only difference between this comparative example and Example 2 is that phenolic resin is not added in S4 and S5. All other steps and conditions are the same as in Example 2, resulting in a cast-type phosphate gradient composite material.

[0089] The cast-type phosphate gradient composite material obtained in this comparative example, after 120 s of oxyacetylene ablation at 2500℃, had a maximum back temperature of 111.8℃, a shear strength of 9.3 MPa, and a thermal conductivity of 0.26 W / (m•K). The results indicate that phenolic resin not only plays a role in organic toughening and interface regulation in the transition and insulation layers, but also affects the pore structure, interlayer bonding, and high-temperature thermal protection performance of the cured slurry.

[0090] Depend on Figure 2 It can be seen that the FCZ cross-section has a complete layered structure and good interface bonding.

[0091] Depend on Figure 3 It can be seen that the microstructure of each layer was characterized by SEM, which verified that the interlayer bonding of each layer prepared by the present invention is tight and the structure is tunable.

[0092] Depend on Figure 4 It can be seen that, by comparing shear strength, FCZ-1 has superior interfacial mechanical properties compared to CZ.

[0093] Depend on Figure 5 It can be seen that, by comparing the ablation process temperature, the FCZ and FCZ-1 of the present invention have stronger heat insulation and ablation resistance than CZ.

[0094] Figures 6-8 The surface, macroscopic and microscopic cross-sections confirmed that the FCZ-1 structure remained stable after high-temperature ablation, with no obvious peeling or delamination damage.

[0095] Depend on Figure 9 It can be seen that the CZ prepared in Comparative Example 1 suffered severe structural damage after ablation.

Claims

1. A castable phosphate gradient composite material, characterized in that: It includes a quartz fiber tube and a phosphate material; the quartz fiber tube is woven from quartz fiber bundles and has a hollow tubular structure; the phosphate material is fixed to the outer surface of the quartz fiber tube and the hollow tubular structure by casting. The phosphate material has a three-layer structure, with a transition layer in the middle and a heat-resistant layer and a heat-insulating layer on both sides, respectively. The heat-resistant layer is formed by mixing and curing boron-modified zirconium-based phosphate slurry, chopped fibers, and hollow microspheres. The transition layer and the heat-insulating layer are both formed by mixing and curing boron-modified zirconium-based phosphate slurry, resin-based organic materials, chopped fibers, and hollow microspheres. Furthermore, the amount of chopped fibers and hollow microspheres increases from the heat-resistant layer to the heat-insulating layer. The boron-modified zirconium-based phosphate slurry is obtained by mixing raw materials including aluminum phosphate, zirconium oxide, boric acid and urea.

2. The cast-type phosphate gradient composite material according to claim 1, characterized in that: The inner diameter of the quartz fiber tube is 10~20mm.

3. The cast-type phosphate gradient composite material according to claim 2, characterized in that: The thickness ratio of the heat-resistant layer, the transition layer and the heat insulation layer is (3~6):(1~4):(3~9).

4. The cast-type phosphate gradient composite material according to claim 1, characterized in that: The chopped fibers include at least one of alumina, quartz fiber, and carbon fiber; The hollow microspheres include at least one of ceramic hollow microspheres and glass hollow microspheres; The resin-based organic compounds include at least one of phenolic resin, epoxy resin, and furan resin; The aluminum-containing phosphate includes at least one of aluminum dihydrogen phosphate and aluminum chromium phosphate.

5. A cast-type phosphate gradient composite material according to any one of claims 1 to 4, characterized in that: The heat-insulating layer is formed by mixing and curing boron-modified zirconium-based phosphate slurry, chopped fibers and hollow microspheres in a mass ratio of (50~80):(0.5~4):(0.5~4); The transition layer is formed by mixing and curing boron-modified zirconium-based phosphate slurry, resin-based organic matter, chopped fibers and hollow microspheres in a mass ratio of (50~80):(2~10):(1~5):(1~5); The heat insulation layer is obtained by mixing and curing boron-modified zirconium-based phosphate slurry, resin-based organic materials, chopped fibers and hollow microspheres in a mass ratio of (50~80):(2~10):(1~6):(1~6).

6. The cast-type phosphate gradient composite material according to claim 5, characterized in that: The boron-modified zirconium-based phosphate slurry contains aluminum phosphate, zirconium oxide, boric acid and urea in a mass ratio of (20~30):(40~60):(1~5):(1~3), and the mixing time is 20~30 min.

7. A method for preparing a cast-type phosphate gradient composite material as described in any one of claims 1 to 6, characterized in that: Includes the following steps: S1 mixes boron-modified zirconium-based phosphate slurry with chopped fibers and hollow microspheres to obtain a heat-resistant layer casting slurry; the heat-resistant layer slurry is cast into the hollow tubular structure and outer surface of a quartz fiber tube, and after vibration and curing, a block sample 1 is obtained; S2 mixes boron-modified zirconium-based phosphate slurry, resin-based organic matter, chopped fibers and hollow microspheres to obtain a transition layer casting slurry; the transition layer slurry is then cast onto block sample 1, and after vibration and curing, block sample 2 is obtained; S3 mixes boron-modified zirconium-based phosphate slurry, resin-based organic matter, chopped fibers and hollow microspheres to obtain a heat insulation layer casting slurry; the heat insulation layer slurry is then cast onto block sample 2, and after vibration and curing, the desired result is obtained. In S1, S2 and S3, the amounts of the chopped fibers and hollow microspheres increase sequentially.

8. The method for preparing cast-type phosphate gradient composite material according to claim 7, characterized in that: The quartz fiber tube is subjected to ultrasonic cleaning pretreatment for 5-8 minutes before use.

9. The method for preparing cast-type phosphate gradient composite material according to claim 8, characterized in that: In S1, the mixing time is 5~10 min, the curing temperature is 60~90℃, and the curing time is 1~2 h; In S2 and S3, the mixing time is 8~15 min, the curing temperature is 60~90℃, and the curing time is 1~2 h.

10. The method for preparing cast-type phosphate gradient composite material according to claim 7, characterized in that: The viscosity of the heat-insulating layer casting grout, the transition layer casting grout, and the heat insulation layer casting grout are all controlled within 100~300 mp·s.

Citation Information

Patent Citations

  • Variable-gradient ablation-resistant heat-prevention and heat-insulation integrated phosphate composite material and preparation method thereof

    CN117024163A